Permeability evolutionary patterns of fractured rock masses in fault zones under seepage-stress coupling - Dekang ZHAO; Bing HAN; Yifan ZENG; Guorui FENG; Yonghong XI; Bofeng CHANG; Zhenghao LI; Pengwei WANG; Lisan WANG (Meitian dizhi yu kantan)
BackgroundIn coal mines, fault structures serve as critical pathways for water inrushes from coal seam floors, posing serious threats to the production safety of mines. Delving into the permeability evolutionary patterns of fractured rock masses in fault zones under seepage-stress coupling holds great significance for the prevention and control of water inrushes along faults from coal seam floors.MethodsAgainst the engineering background of the Gaohe Coal Mine under the Shanxi Lu’an Mining (Group) Co., Ltd. in Shanxi Province, this study analyzed the microscopic physical properties and the pore and fracture structures of a fractured rock mass in a fault zone initially. Then, using triaxial seepage tests, this study investigated the permeability evolutionary patterns of the fractured rock mass under cyclic loading and unloading, establishing the quantitative coupling relationship between the permeability coefficient and the confining pressure. Finally, based on the mechanical model analysis, this study constructed a numerical model for water inrushes along fault Fw159 in the Gaohe Coal Mine. Accordingly, the formation and evolution patterns of pathways for water inrushes from coal seam floors were analyzed. Results and Conclusions The pores and fractures in the fractured rock mass of the fault zone exhibited complex structures, rough edges, and non-directional development microscopically, and these characteristics governed the permeability of the rock mass. A negative exponential relationship was observed between the permeability coefficient and the confining pressure, with the variations in the seepage pressure playing a significant role in the displacement of the fractured zone in the floor and the formation of hydraulically conductive pathways. During coal mining, stress disturbance preceded the displacement effect, which became gradually pronounced after mining-induced stress peaked. As pore water pressure reached 3 MPa, confined water accumulated at the bottom of fault Fw159, migrating upward along the fractured zone of the fault until instability failure occurred. The results of this study reveal the inherent relationships between the permeability characteristics of fractured rock masses in fault zones and the water inrushes along faults from coal seam floors in coal mines, providing a theoretical basis for the prevention and control of water inrushes from coal seam floors and safe mining in coal mines.